Public Perception of the Policy of Banning Eid Al-Fitr in 2021 in Bogor Regency - Muhamad Alfi Auliya Rachman (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Introduction: Homecoming is a social phenomenon in Indonesia every year. To prevent the spread of the Covid-19 virus, the Government makes a Policy to Eliminate Homecoming for Eid Al-Fitr in 2021. Objective: To determine public perceptions regarding the ban on going home for Eid in 2021. Methods: This study uses a survey method with a quantitative questionnaire conducted at the Type C Hospital in Bogor Regency with a sample of 84 respondents. Results: respondents aged 30-40 years agreed not to go home for Eid with a presentation of 80%, over 40 years of age 75% agreed and 25% did not agree. Conclusion: During the Covid-19 Pandemic, greatly affects people's perceptions of traveling back and forth. The majority of respondents agreed to the 2021 Eid homecoming ban due to concerns about contracting or transmitting the Covid-19 virus. Recommendations: There are strict sanctions for violators who continue to go home, scouring the location of crowds during the Eid transportation period, the community continues to maintain health and comply with the Health Protocol.